The King of Uzbek Prose - Pazilovich Lafasov , Urak (International Journal of Psychosocial Rehabilitation, 2020)
This article explains that after the novels of the great Uzbek writer Abdullah Qadiri, the concept of “Uzbek novels” appeared in world literature. The author bases his opinion on the well-grounded commentary of the literary scholar E.E. Bertels. In turn, Uzbek classical literature explains that epic works were created in the 14th-15th centuries by Nosiriddin Rabguzi and Poshshokhoja Khoja and at the beginning of the 20th century by Hamza Hakimzoda and Sadriddin Ayni. It is said that Qadiri first contributed to the genre of storytelling and satirical writing and then began to write national novels. For this purpose the author has studied the works of Husain Javid and Jorji Zaydon from Oriental literature and Walter Scott novels from Western literature. At the same time, Abdullah Qadiri wrote that he had written novels and founded the Uzbek National School of Romance. At the same time, the writer confirmed in his novel “The Days Gone by” that it inspired the Uzbek people to national freedom. It also says that the author found a source of support for the novel, undertakes the obligation to share a new spirit with the novel, and the theme is relevant to the realities of the work. Also, the Uzbek-speaking culture of privacy, the secret of love, the end of secret love with the Shari’a, the habit of consulting with a white milk mother in Uzbekistan, the tradition of greetings after the wedding, the beauty of the Uzbek wedding, and the responsibility of the bridegroom. And cases such as a bride’s satisfaction with marriage were commented on. In the next place are the thoughts of the proud mother of the bride, the mother’s use of paternity, the sincere father-son relationship, the pride, the fake letter of the enemies, the cheating of the father-in-law, the disclosure of the secret, and the love of the couple. The unseen dream, the scheming of the woman, the misery, the bitter note on the floor, and the mourning of the mothers of Uzbekistan were highlighted. In turn, Abdullah Qadiri’s invaluable literary skills were proven, such as choice of words, prototype search, test of the power of influence in his psyche, unique art, eventuality, image accuracy, and proof of reality. In the conclusion it is acknowledged that the nationality of the Uzbek son of Abdullah Kadiri was revealed, his self-sacrifice was sacrificed in this honorable way, and he remains a pride of his nation for his courage and patriotism.